Simple interrupted vs figure of eight suturing in open method extraction - MALAY, KAUSALYAH KRISNA; R.N, BALAKRISHNAN; KUMAR.V, JAYANTH (The journal of contemporary issues in business and government, 2021)
Development of infections along the line of the incision is potentially a dangerous postoperative event. However, some infections that affect the wound margins in certain areas of the body may put the prognosis, in terms of the patient's life, at risk. In less dramatic situations they in case delay healing of tissues involved in transalveolar extraction. The suturing techniques used to reconstruct the planes for primary healing. To evaluate the prevalence of simple interrupted sutures and figure of eight sutures in transalveolar extraction. To analyse the use of simple interrupts and figure of eight sutures. The study was conducted as a hospital based case control study in the area of Thiruverkadu, Chennai. The study was carried out by collecting data by reviewing patients data and analysing the data of 86000 patients between June 2019 and March 2020 at the private dental institute. A total number of 326 case sheets were taken for the study after reviewing from intraoral photographs and additional supports. Photographs were accessed to determine the suturing techniques for patients that underwent open method extraction. Pearson Chi Square Test was evaluated using SPSS. Results were recorded. Simple interrupted suture was commonly used compared to figure of eight suture in transalveolar extraction in the private dental college. Majority of the dental students placed simple interrupted sutures compared to figure of eight sutures postoperative to open method extractions.